Socialization of Logistics in the World of Business to SMA/K Students of Tabanan District - Putu Diva Ariesthana Sadri; Nengah Widiangga; Ni Luh Darmayanti; Dynes Rizky Navianti; Bambang Widjonarko (Jurnal Peduli Masyarakat, 2022)
In this current era, Community Service (PKM) is a very useful thing to improve the quality of people's lives, the logistics business has become the center of attention of the community with very rapid growth, companies that provide transportation services for delivery of goods from pickup to destination , this condition requires high school students. The success of business management is highly dependent on the expertise of business people to develop insights about the logistics business itself, strategically managing the logistics business process for material procurement, either by organizing procurement, moving or storing related materials and information, and marketing networks. Limited knowledge is one of the challenges that must be faced by business people in managing their business. The Bali Land Transportation Polytechnic carries out community service activities to SMA 1 Baturiti, Tabanan Regency by referring to Logistics in the Business world in increasing students' knowledge of logistics in the business world. With this PkM socialization, the expected goal is to increase students' knowledge of logistics in the business world, and what types of businesses exist in logistics in the business world and how to make decisions about the logistics business and are expected to be considered in the field later. This activity is carried out using the mediation method with counseling which aims to increase understanding and awareness of the logistics world. From this method it is expected that students are able to create a business and work opportunity in the logistics world.